ROUTING OF A MULTI-ROTOR UAV USING AN AIRBORNE AUTOMATIC SERVICE STATION WHILE MONITORING THE TERRITORY OF A POTENTIALLY DANGEROUS OBJECT - Fesenko, H. V. (Systems and Technologies, 2019)
Multi-rotor UAVs have advantages over other UAVs because of their capability of hovering, which is essential to guarantee more accuracy of the given parameters measurement when performing monitoring missions. However, such UAVs have low battery life and should be able to replace or recharge their batteries on the route. The paper is devoted to the development of an approach to determine the optimal routing of a multi-rotor UAV, which uses an airborne automatic service station (АASS) for its batteries replacement. On the basis of the analysis of the peculiarities of the use of auto-matic service stations, a faceted classification one of their types – automatic energy re-covery stations – was proposed. The following classification features were used: princi-ple of operation, method of replenishment of energy, method of recharging, type of bas-ing, type of construction, number of places for simultaneous UAV service. The example of application of the proposed approach for monitoring of 11 control posts of Za-porizhzhia NPP is given. The DJI Mavic 2 Enterprise Dual UAV, which travels at a speed of 40 km/h and has a battery life of 31 minutes, was selected for the monitoring mission. The AASS based on the SL-231 Scout helicopter, which travels at 100 km/h and is capable of operating in unmanned mode, was used to replace the UAV batteries on the route. The following results were obtained: the shortest flight route to visit all the specified monitoring points calculated by solving the traveling salesman problem and indicated on the map; a compatible UAV and АASS route schedule; a separate АASS route schedule. The total time of the UAV monitoring mission and the total time of the АASS mission to ensure the replacement of the UAV batteries were calculated. The pro-posed approach and the software developed for its implementation can be used by ground control station operators to develop optimal routes for the joint use of UAVs and АASS while monitoring the specified points of potentially dangerous objects. Further studies should include options for monitoring the specified points of potentially danger-ous objects by UAV and АASS fleets for reducing the overall monitoring mission time.